Amada puta: reescribiendo el matrimonio, la maternidad y la identidad en Filumena Marturano, de Eduardo De Filippo - De Angelis, Rose (Revista de Antropología Social, 2008)
Eduardo De Filippo’s 1946 play Filumena Marturano, situated in the war-ravaged city of Naples, begins with a heated discussion between Domenico Soriano, a middle-aged business man, and Filumena Marturano, his mistress, a woman who, after spending twentyfive years as his de facto wife, has finally tricked him into marriage. Filumena will eventually transform what society has designated as aberrant sexuality to traditional morality and rewrite herself as wife and mother to the three sons she has had out of wedlock. In true neorealist tradition, de Filippo takes a panoramic view of a society, devastated by war and still divided by class distinctions, in which the family becomes the vehicle to and the reason for survival. Filumena, like Naples itself, rises from the ruins of the past and emerges triumphant not in the idealism of happily-ever-after but in neorealist fashion -with a renewed consciousness, collective action, and the belief in the inevitability of future reconciliations.